Street angel - China Video Movies Distributing Co. (San Francisco : China Video Movies Distributing Co., 1983)
Takes place in the slums of Shanghai in 1935. Describes the friendship of a street musician, his friends, and two unfortunate sisters.
VHS format.
Title from container ; title also in Chinese.
Videocassette release of the 1937 motion picture.
Zhao Dan ; Wei Heling ; Zhou Xuan.
Keywords: Feature films